2019
DOI: 10.1016/j.buildenv.2019.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a fragrant tree on the perception of traffic noise

Abstract: This study investigated the effect of a fragrant tree on the perception of traffic noise, aiming to reveal the interaction between odour and sound in urban environment. Field research investigations including on-site measurement and questionnaire distribution were conducted in two conditions (with and without fragrance) in four streets in Harbin, China, where lilac had been planted. The results showed that fragrance could affect the perception of traffic noise, which was reflected in increased overall comfort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 33 publications
0
23
0
1
Order By: Relevance
“…Of the 42 subjects, one had to go to a Taekwondo class and failed to complete all the experiments due to time conflicts, so the data of a total of 41 subjects were collected. A database containing the final results was created using IBM SPSS 25.0 [27,31,50,51] to evaluate the effect of different types of alarm sounds on the risk perception of the children in the evacuation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 42 subjects, one had to go to a Taekwondo class and failed to complete all the experiments due to time conflicts, so the data of a total of 41 subjects were collected. A database containing the final results was created using IBM SPSS 25.0 [27,31,50,51] to evaluate the effect of different types of alarm sounds on the risk perception of the children in the evacuation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Although the very large number of stimulus conditions (N = 129) that were assessed in their study makes the drawing of any simple conclusions difficult, taken together, the complex array of significant findings reported nevertheless clearly do suggest that sound and scent can interact in terms of influencing people's evaluation of urban design (see also Ba and Kang, 2019b). Ba and Kang (2019a, p. 314) concluded that: "For the overall evaluation, in the presence of birdsong and low-volume sound, the overall evaluation was unaffected by odor; for other combinations of sound and odor, with increased concentration, the overall evaluation improved.…”
Section: Smell In the Multisensory Built Environmentmentioning
confidence: 99%
“…This is probably due to the psychological influence of vegetation (people feel good and safe among greenery), as also observed by Brambilla and Maffei [104] and Van Renterghem [62], who showed the importance of the compliance of sounds heard in parks with the expectations of visitors and audiovisual interaction with regard to the sound pressure level. Moreover, the smell of trees may play an important role in the perception of noise [105]. This factor, however, was not taken into account in the research conducted in the parks in Olsztyn.…”
Section: Discussionmentioning
confidence: 99%